(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2005)
Patients of a mental hospital stay in mental hospital wards during their ill-treatment time. The hope is that they can be recovered or at least their "illness" can be minimal before they involve in the rehabilitation process. It has been found out, according to this study, that some aspects of the elements of the interior of the ward affect negatively to the safety and security of adult patients. For example, in the means of safety, the patients might injure or be injured by another patients; while in the means of security, the patients might run away from the ward. This study has been conducted at P3/2nd Class mental hospital ward of Prof. dr. Soeroyo Mental Hospital of Type A in Magelang, Central Java. Because there is no standardized design in the interior of mental hospital wards, the findings of this study can be recommended only for the hospital has been studied. But when the wards of any other mental hospitals have similar characteristics in the interior with the interior of the ward under studied, then it can also be recommended for them. Abstract in Bahasa Indonesia : Bangsal suatu Rumah Sakit Jiwa (RSJ) digunakan sebagai tempat tinggal untuk pasien mental rawat inap. Harapannya ialah bahwa pasien mental akan bisa disembuhkan, atau paling tidak diperkecil "sakit"nya sebelum mengikuti proses rehabilitasi. Namun dari penelitian ditemukan bahwa justru aspek-aspek pada elemen tata ruang dalam bangsal itu sendiri yang bisa memberikan pengaruh negatip terhadap keselamatan dan keamanan pasien mental dewasa. Dalam hal keselamatan pasien mental dewasa antara lain memudahkan pasien untuk terlukai atau melukai sesama pasien. Dalam hal keamanan pasien mental dewasa antara lain memudahan pasien untuk melarikan diri. Penelitian ini dilakukan pada bangsal P3/Klas 2 Rumah Sakit Jiwa Tipe A Prof. dr. Soeroyo di Magelang, Jawa Tengah. Temuan-temuan penelitian ini direkomendasikan untuk RSJ yang dipakai sebagai studi, namun tidak tertutup kemungkinan untuk direkomendasikan bagi RSJ yang lain bila terdapat kesamaan karakteristik pada tata ruang dalam bangsalnya, karena memang tidak ada standar baku untuk RSJ. Kata kunci: bangsal RSJ, aspek-aspek pada elemen tata ruang dalam, pasien mental dewasa, keselamatan, keamanan.